EDUCATIONAL MATERIAL IN TEACHING COMMUNICATIVE ABILITIES TO STUDENTS AND THEIR CONTENT - Sariev A. B. (Galaxy International Interdisciplinary Research Journal, 2024)
The article touches upon the most important issues of the theory of teaching students communicative abilities on the basis of tasks, exercises, describes the technology of their fulfilment. The authors have highlighted the characteristic features of students, which should be taken into account in the learning process and which directly affect the qualitative organisation of work with educational material.